Synthesis of Metal Boranes as Solid-State Electrolytes for Next Generation Battery Applications - Holanda Pereira de Souza, Diego (Curtin University, 2022)
Modifying conventional batteries by replacing liquid electrolytes with solid ionic conductors is a novel strategy for developing next-generation energy storage devices (solid-state batteries) with increased safety, energy density, and reduced costs. Metal-boranes have shown promising features as solid-state electrolytes, due to their high ionic conductivity and compatibility with alkali-metal anodes. The synthesised metal-boranes demonstrate promising properties for further research and application as solid-state electrolytes in batteries.